Implementation of Fingerprint Biometrics for Secure Contactless Banking Card Transactions - Ibrahim, Soleen J.; Abdulkareem, Shaheen A.; Al-Khalil, Ahmad B. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2026)
A contactless card is an easy and straightforward way to make a purchase that takes only a few seconds without requiring a Personal Identification Number (PIN) or signature. However, not requiring a PIN or signature on a contactless bank card makes it vulnerable to fraud attacks when losing or stealing the card. This article delivers a new model which is developed for securing a bank contactless card with fingerprint authentication. The suggested model is the creation of a new fingerprinting algorithm that combines with the virtual contactless card. The fingerprint recognition algorithm employs image processing methods to enhance and extract features in order to compare fingerprint impression images. The performance of the proposed model is evaluated based on two metrics: false acceptance rate and false rejection rate. There are five scenarios to test and evaluate the proposed model. The findings establish that the developed system enhances the process of embedding biometrics (fingerprints) to non-contact smart card and a user-friendly experience.